Response of Water Conservation Strategies on Soil-Water-Plant Relationships in Degraded Farmlands (Case study : Southeast Iran) - Jahantigh, Mansour; Jahantigh, Moien (Annals of Arid Zone, 2025)
At present, land degradation is a major challenge in arid regions that cause serious environmental problems. This study seeks to provide an adaptive approach using water conservation practices (drought-tolerance plant establishment) for sustainable land management (SLM) in arid areas. The plant growth characteristics of Citrullus colocynthis under clay-pot and traditional irrigation methods have been analyzed and interpreted for their conservation effects over a three-year period, from 2019 to 2021. The results indicate that soil moisture levels under clay-pot irrigation increased by 49%, 39%, and 56% at depths of 10 cm, 30 cm, and 50 cm, respectively, compared to the traditional irrigation method. This led to a significant improvement in water use efficiency, which was 1.7 times greater, and a reduction in water consumption by threefold compared to the control treatment. Clay-pot irrigation led to a significant decrease in soil hydrogen potential, electrical conductivity, and sodium levels compared to the traditional irrigation method (p ≤0.05). Field observations revealed that C. colocynthis had exceptional growth performance during prolonged drought seasons, and growth characteristics such as fruit yield and canopy cover significantly increased (2.02, 2.12 and 7.6, 8.3 times more than the first growth season, respectively). In addition, following plant establishment, organic carbon increased up to 19% and 38% compared to the first year respectively. Overall, the results of this study depicted that, water conservation techniques such as clay-pot irrigation and establishment of drought-tolerant plants (C. colocynthis species) has a positive effect on soil-water-plant relationships, and play a key role in sustainable land management in degraded farmlands